Socio-Economic Analysis Of Guava Farmers’ Welfare (Psidium Guajava) In Sei Semayang Village, Dusun XVII Sempat Arih Sunggal District, Deli Serdang Regency - Dea Ameylia; Ahmad Fadlan; Annisa Ilmi Faried (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to examine the impact of socioeconomic factors on the welfare of guava farmers (Psidium guajava) in Sei Semayang Village,Dusun Xvii Sempat Arih Sunggal District, Deli Serdang Regency. The variables analyzed include income, labor, and education level. This research employed a quantitative approach using a survey method involving 100 respondents. Data were analyzed using Exploratory Factor Analysis (EFA) and multiple linear regression with SPSS version 25. The results indicate that income and education level have a positive and significant effect on farmers’ welfare, while labor does not have a significant effect. Simultaneously, all variables significantly influence welfare, with an Adjusted R Square value of 0.423, indicating that 42.3% of the variation in welfare can be explained by the model. These findings suggest that improving income and education plays a crucial role in enhancing the welfare of guava farmers.